A NEW PROCEDURE FOR CANNING OF SQUIDS - RAGHUNATH, M R; SOLANKI, K K (Fishery Technology, 2017)
A new canning procedure for squid mantles aimed at increasing the :fiU and retaining the sweet flavour of squids was evolved. In the new method, after blanching smaller mantles are inserted inside bigger ones to reduce voids and thus increase the fi.U to 56% and above as compared to 46% when packed as rings. In addition, spent blanching medium containing desirable flavour constituents of squid was modified and used as covering medium which increased the flavour of canned product.